Multiscale Co‐reconstruction of Lung Architectures and Inhalable Materials Spatial Distribution. Issue 8 (8th February 2021) - Sun, Xian; Zhang, Xiaochuan; Ren, Xiaohong; Sun, Hongyu; Wu, Li; Wang, Caifen; Ye, Xiaohui; York, Peter; Gao, Zhaobing; Jiang, Hualiang; Zhang, Jiwen; Yin, Xianzhen
Abstract: The effective pulmonary deposition of inhaled particulate carriers loaded with drugs is a prerequisite for therapeutic effects of drug delivery via inhalation route. Revealing the sophisticated lung scaffold and intrapulmonary distribution of particles at three‐dimensional (3D), in‐situ, and single‐particle level remains a fundamental and critical challenge for dry powder inhalation in pre‐clinical research. Here, taking advantage of the micro optical sectioning tomography system, the high‐precision cross‐scale visualization of entire lung anatomy is obtained. Then, co‐localized lung‐wide datasets of both cyto‐architectures and fluorescent particles are collected at full scale with the resolution down to individual particles. The precise spatial distribution pattern reveals the region‐specific distribution and structure‐associated deposition of the inhalable particles in lungs, which is undetected by previous methods. Overall, this research delivers comprehensive and high‐resolution 3D detection of pulmonary drug delivery vectors and provides a novel strategy to evaluate materials distribution for drug delivery. Abstract : Effective deposition of inhaled drug carriers is a prerequisite for intrapulmonary drug delivery systems. The cross‐scale structures of lungs from alveoli to whole organ and region‐specific distributions of the inhalable particles are revealed with an unprecedented resolution by the fluorescence‐micro optical sectioning tomography and image data mining, which provide a novel strategy to evaluate materials distribution for particulate drug delivery.